Sobre David Charles Wright-Carr y Francisco Marco Simón (eds.), From Ancient Rome to Colonial Mexico. Religious Globalization in the Context of Empire - Ortiz-Delgado, Francisco Miguel (Historia Mexicana, 2024)
-